2008
DOI: 10.1002/jssc.200700458
|View full text |Cite
|
Sign up to set email alerts
|

HPLC‐F analysis of melatonin and resveratrol isomers in wine using an SPE procedure

Abstract: An original analytical method has been developed for the determination of the antioxidants trans-resveratrol (t-RSV) and cis-resveratrol (c-RSV) and of melatonin (MLT) in red and white wine. The method is based on HPLC coupled to fluorescence detection. Separation was obtained by using a RP column (C8, 150 mm x 4.6 mm id, 5 mum) and a mobile phase composed of 79% aqueous phosphate buffer at pH 3.0 and 21% ACN. Fluorescence intensity was monitored at lambda = 386 nm while exciting at lambda = 298 nm, mirtazapin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
82
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 36 publications
7
82
2
1
Order By: Relevance
“…These amounts were higher than values found by another study [42] carried out on wines after the fermentation of musts obtained from three grape varieties (Sangiovese, Albana and Trebbiano).…”
Section: Ability Of S Cerevisiae Strains To Produce Bioactive Compoucontrasting
confidence: 71%
“…These amounts were higher than values found by another study [42] carried out on wines after the fermentation of musts obtained from three grape varieties (Sangiovese, Albana and Trebbiano).…”
Section: Ability Of S Cerevisiae Strains To Produce Bioactive Compoucontrasting
confidence: 71%
“…3,4 Numerous analytical methods were reported for detection and quantification of melatonin, such as ultraviolet-visible (UV-vis) spectrophotometry, chemilumenescence, fluorometry, thin-layer chromatography, gas chromatography-mass spectrometry, and high-performance liquid chromatography. [5][6][7][8][9] Furthermore, melatonin is an antioxidant compound that can be analyzed with electrochemical methods. 10 Voltammetric and amperometric methods were applied for the determination of melatonin using carbon paste electrodes, carbon disk electrode, carbon fiber microdisk electrode, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[10,26] We also expect melatonin to concentrate in the skin and seeds of grapes. Thus, with levels of melatonin in various seed types all <200 ng·g -1 , [27] good agreement by different research groups on grape skin melatonin contents near or below 1 ng·g -1 , [23,24] and finished wine concentrations of up to 0.5 ng·mL -1 , [24,28] whole grape concentrations of 100,000 to 200,000 ng·g -1 as reported by Murch et al do not seem reasonable. [22] Furthermore, the authors claim the highest melatonin concentrations were found at the early stage of veraison, yet a statistical reanalysis of their data shows there is no significant difference in mean concentrations between the four stages of development (p>0.45 by one-way ANOVA).…”
mentioning
confidence: 64%